No plastic bags? The policy challenge of changing consumer (and corporate) behaviour for future sustainability / Cameron Richards and Irina Safitri Zen - Richards, Cameron; Safitri Zen, Irina (Faculty of Administrative Science and Policy Studies, 2012)
In order to implement policies of sustainability to change consumer behavior, governments must also gain sufficient support from various stakeholders across the wider community as well as the private sector. In Malaysia as elsewhere government campaigns to encourage shoppers to stop using plastic bags illustrates not only the challenges of getting the community to ‘go green’ but also to sustainably change consumer behavior. The ‘no plastic bags’ campaign began in several Malaysian states before being adopted as a national policy direction. This paper will discuss this process in terms of the wider challenge of public education or awareness campaigns as government policy-building for future sustainability. It will also consider the role that corporate social responsibility policies play in the support provided for such campaigns by participating shops, supermarkets and shopping centres.